Pengembangan Sistem Informasi Penilaian Kinerja Guru Menggunakan Metode Rational Unified Process (RUP) Berbasis Web (Studi Pada SD Negeri Prigen 1) - Axel Reinno Fabiyanto; Yusi Tyroni Mursityo; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
SD Negeri Prigen 1 is a basic education institution located in Pasuruan Regency. SD Negeri Prigen 1 has human resource covering a teacher. Teacher must be improve their abilities and skills in appliying the competencies needed in the learning process. Teacher performance assesment is needed to identify the teacher's ability to carry out his duties through the measurement of the competency mastery shown. Teacher performance assesment at SD Negeri Prigen 1 still has a number of problems that can interfere the process of teacher performance asessment such as still using conventional system, that is a difficult calculation process, make a report and recapitulation. An information system is needed to solve these problems. In developing this system using the RUP method because in order to balance between the needs and priorities of stakeholders and system requirements that are not clear. The teacher assessment information system produces a number of 19 features. Black box testing successfully tested 43 items of validation tests that were valid, while compatibility testing resulted in several minor and major issues in some browsers. UAT gets the final result of 90% or strongly agrees to be accepted by the user. Therefore, the existence of an information system evaluating the performance of teachers can solve problems such as the process of evaluating teacher performance more quickly, efficiently and simplify the process of making reports.